Early reduction of pulmonary arterial hypertension in patients using a long-term mechanical ventricular assistance device: a cross-sectional study - Rangel, Bruno Soares da Silva (2022)
BACKGROUND: Severe pulmonary arterial hypertension (PAH) is a contraindication for heart transplantation (HT). It has been correlated with increased early and late mortality, mainly associated with right ventricular failure. Ventricular assistance devices (VADs) can promote reduction of intracardiac pressures and consequent reduction of PAH over the medium and long terms, thus enabling future candidature for HT. The diminution of early pulmonary pressure within this scenario remains unclear. OBJECTIVE: To evaluate the reduction of PAH and correlate data from right catheterization with the earliness of this reduction. DESIGN AND SETTING: Cross-sectional study in a general hospital in São Paulo, Brazil. METHODS: This was a retrospective analysis on the medical records of patients undergoing VAD implantation in a single hospital. Patients for whom VAD had been indicated as a bridge to candidature for HT due to their condition of constant PAH were selected. RESULTS: Four patients with VADs had constantly severe PAH. Their mean pulmonary artery systolic pressure (PASP) before VAD implantation was 66 mmHg. Over the 30-day period after the procedure, all the patients evolved with a drop in PASP to below 60 mmHg. Their new average was 36 mmHg, which was a drop of close to 50% from baseline values. The one-year survival of this sample was 100%. CONCLUSION: VAD implantation can reduce PAH levels. Early reduction occurred in all patients. Thus, use of VAD is an important bridge tool for enabling candidature for HT among patients with constantly severe PAH.